Single atom and defect engineering of CuO for efficient electrochemical reduction of CO2 to C2H4. Issue 1 (24th March 2022) - Chu, Senlin; Kang, Changwoo; Park, Woonghyeon; Han, Yu; Hong, Song; Hao, Leiduan; Zhang, Hao; Lo, Tsz Woon Benedict; Robertson, Alex W.; Jung, Yousung; Han, Buxing; Sun, Zhenyu
Abstract: Electrochemical CO2 transformation to high‐value ethylene (C2 H4 ) at high currents and efficiencies is desired and yet remains a grand challenge. We show for the first time that coupling single Sb atoms and oxygen vacancies of CuO enable synergistic electrocatalytic reduction of CO2 to C2 H4 at low overpotentials. Highly dispersed Sb atoms occupying metal substitutional sites of CuO are synthesized under mild conditions. The overall CO2 reduction faradaic efficiency (FE) reaches 89.3 ± 1.1% with an FE toward C2 H4 exceeding 58.4% at a high‐current density of 500 mA/cm 2 . Addition of the p‐block metal is found to induce transformation of CuO from flakes to nanoribbons rich in nanoholes and oxygen vacancies, greatly enhancing CO2 adsorption and activation while suppressing hydrogen evolution. Further density functional theory calculations with in situ X‐ray diffraction reveal that combining Sb sites and oxygen vacancies prominently lessen the dimerization energy of adsorbed CO intermediate, thus boosting the conversion of CO2 to produce C2 H4 . This study provides a new perspective for promoting selective C–C coupling for electrochemical CO2 reduction. Abstract : We demonstrate synergistic electrocatalytic reduction of CO2 to C2 H4 by engineering single Sb atoms and defects of CuO. The overall CO2 reduction faradaic efficiency (FE) approaches 89.3 ± 1.1% with an FE toward C2 H4 over 58.4% at 500 mA/cm 2 . This study is expected to provide useful insights into the design and construction of advanced electrocatalysts for CO2 electrolysis.